Monitoring Methane CH4 and Carbon Dioxide CO2 Concentrations at Wonorejo Compost Center - Gaudentius Indra Ardhanu Bota; Okik Hendriyanto Cahyonugroho (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Composting organic waste can generate greenhouse gases, such as methane (CH4) and carbon dioxide (CO2), which may affect environmental quality and public health. This study aims to design and implement an Internet of Things (IoT)-based monitoring system for CH4 and CO2 concentrations at Wonorejo Kompos Center. The system utilizes an ESP32 microcontroller integrated with MQ-4 and MQ-135 gas sensors. Measurement data are displayed on an LCD and transmitted to cloud-based storage via a WiFi connection. Data collection was conducted over 2 weeks with a 4-hour measurement interval. The results indicate that the average CO2 concentration was approximately ±106 ppm, while CH4 concentrations ranged from 0.01 to 0.09 ppm. Comparison with gas chromatography (GC) laboratory analysis shows differences in absolute values; however, the IoT system consistently captures gas concentration trends. This system demonstrates potential as a real-time greenhouse gas monitoring solution in organic waste processing facilities.Contribution to Sustainable Development Goals (SDGs):SDG 11: Sustainable Cities and CommunitiesSDG 12: Responsible Consumption and ProductionSDG 13 : Climate Action